ISU GENDER, IDENTITAS DAN KULTURAL DI AFRIKA DAN TIMUR TENGAH DALAM TIGA KARYA: DREAMS OF TRESPASS, MY SALWA MY PALESTINE, INSIDE THE KINGDOM - Raghib Fadhil; Salma Fauziah Rahmalia; Salsabila Fauziyah Ihya; Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This study aims to uncover how the analyzed literary works present cultural issues occurring in the Middle East and Africa.